Characterizing Methyl‐Bearing Side Chain Contacts and Dynamics Mediating Amyloid β Protofibril Interactions Using 13Cmethyl‐DEST and Lifetime Line Broadening1. (11th August 2014) - Fawzi, Nicolas L.; Libich, David S.; Ying, Jinfa; Tugarinov, Vitali; Clore, G. Marius
Abstract Many details pertaining to the formation and interactions of protein aggregates associated with neurodegenerative diseases are invisible to conventional biophysical techniques. We recently introduced 15N dark‐state exchange saturation transfer (DEST) and 15N lifetime line‐broadening to study solution backbone dynamics and position‐specific binding probabilities for amyloid β (Aβ) monomers in exchange with large (2–80 MDa) protofibrillar Aβ aggregates. Here we use 13Cmethyl DEST and lifetime line‐broadening to probe the interactions and dynamics of methyl‐bearing side chains in the Aβ‐protofibril‐bound state. We show that all methyl groups of Aβ40 populate direct‐contact bound states with a very fast effective transverse relaxation rate, indicative of side‐chain‐mediated direct binding to the protofibril surface. The data are consistent with position‐specific enhancements of 13Cmethyl‐<alternatives> <![CDATA[${R{{{\rm tethered}\hfill \atop 2\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgh1c9nv0bn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> values in tethered states, providing further insights into the structural ensemble of the protofibril‐bound state.